The Impact of Counsel at First Appearance on Pretrial Release in Felony Arraignments: The Case of Rural Jurisdictions. (July 2020) - Worden, Alissa Pollitz; Shteynberg, Reveka V.; Morgan, Kirstin A.; Davies, Andrew L. B.
This article examines the impact of early provision of counsel on judges' pretrial release and bail decisions in two rural counties in upstate New York, in cases involving felony charges. This study builds upon previously reported research on misdemeanor cases. We note that although the stakes are higher in felony cases, few studies have investigated the dynamics of first appearance decisions at either level. We investigate the hypotheses that when defendants are represented by attorneys at their first appearances in court, (a) judges are more inclined to release on recognizance or under supervision, (b) judges impose less restrictive bail amounts, and (c) as a consequence, defendants spend less time detained prior to disposition. We find mixed support for these hypotheses, although some evidence that counsel at first appearance (CAFA) produces the expected outcomes. We conclude that the implementation of programs intended to ensure CAFA may be tempered by courthouse cultures, and that future research on court reform should include the study of rural jurisdictions.